2013
DOI: 10.1186/1477-7819-11-208
|View full text |Cite
|
Sign up to set email alerts
|

Primary chondrosarcoma of the breast: a case presentation and review of the literature

Abstract: Mammary sarcomas are uncommon tumors. When tumors like malignant cystosarcomaphyllodes and metaplastic carcinoma, where malignant cartilaginous areas may be present, are excluded, only nine cases have been reported to date.We report another case of primary chondrosarcoma of the breast here. A 24-year-old Mediterranean woman presented with a painful mass in the right breast and a physical examination revealed a palpable mass. An incisional biopsy was performed and primary chondrosarcoma was diagnosed based on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Sarcomas arise from the stromal tissue of the mammary gland and if angiosarcoma, which has a more severe prognosis, is excluded, the course of the disease is not significantly different compared with tumors arising from other sites ( 2 ). Chondrosarcoma is a rare type of sarcoma that, to the best of our knowledge, was reported in only five cases in the literature prior to 2001 ( 3 – 6 ) and 11 cases in the literature between 2002 and 2013 ( 7 17 ), and mainly occurs in females >50 years old. Macroscopically, chondrosarcoma appears as a whitish-gray, round mass with regular margins and necrotic, hemorrhagic or cystic areas that is characterized by rapid growth, although the sarcoma rarely invades locally or metastasizes to lymph nodes ( 9 – 13 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 91%
“…Sarcomas arise from the stromal tissue of the mammary gland and if angiosarcoma, which has a more severe prognosis, is excluded, the course of the disease is not significantly different compared with tumors arising from other sites ( 2 ). Chondrosarcoma is a rare type of sarcoma that, to the best of our knowledge, was reported in only five cases in the literature prior to 2001 ( 3 – 6 ) and 11 cases in the literature between 2002 and 2013 ( 7 17 ), and mainly occurs in females >50 years old. Macroscopically, chondrosarcoma appears as a whitish-gray, round mass with regular margins and necrotic, hemorrhagic or cystic areas that is characterized by rapid growth, although the sarcoma rarely invades locally or metastasizes to lymph nodes ( 9 – 13 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 91%
“…Primary chondrosarcoma of the breast, although very rare, has been reported previously 1. An extensive review of 132 636 cases of breast cancer between 1973 and 1998, in the Netherlands,2 identified 34 cases of concurrent breast cancer and cartilaginous tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Breast sarcomas are rare; they represent a heterogenous group of tumours, with a prevalence of 0.5% of all breast tumours, and in particular the primary breast chondrosarcomas are extremely uncommon. In literature just few cases of primary breast chondrosarcoma are reported [1] , [2] , [3] , [4] , [5] , the case described here should be the first that includes all imaging findings: mammography, ultrasound and MRI. Breast-MRI is useful to revealed abnormal lymph nodes, invasion of the pectoral muscle and/or skin, but it does not add any important information about the nature of the mass, even if the absence of CE in the central part of the mass could suggest a necrotic and/or condroid area as confirmed by the histologic pattern performed after surgical removal of the mass.…”
Section: Discussionmentioning
confidence: 99%
“…Breast sarcomas are uncommon and in particular the primary breast chondrosarcoma is extremely rare [1] , [2] , [3] , [4] , [5] . They represent a challenge for physicians because the diagnosis and the decision of the preferred surgical treatment are often difficult being not common.…”
Section: Introductionmentioning
confidence: 99%